Unrecognised urinoma caused by infiltrative bladder cancer - Grbić Dragan; Jeremić Dimitrije P.; Vojinov Saša; Levakov Ivan; Cantrell Alexander B.; Marušić Goran (Vojnosanitetski Pregled)
Introduction. Urinoma develops after disruption of collecting system of urinary tract and urine leak in surrounding tissue. Most common causes of urinoma are blunt or penetrating trauma. Less common causes are iatrogenic injuries or urinary tract obstruction. In this article we presented a rare case of the urinoma caused by infiltrative bladder cancer. Case report. Acutely ill, a septic patient with ileus and profound azothaemia was admitted to medical intensive care unit. Native computed tomography revealed moderate ileus, right kidney hydronephrosis, extensive retroperitoneal urinoma and vesical thickening with excluded infiltration of ureteral orifices. Computed tomography guided percutaneous drainage was done. Upon stabilization, patient underwent transurethral bladder tumor electroresection (histopathology report was: infiltrative transitional cell tumor of urinary bladder). Radical cystectomy was done. The patient’s recovery was uneventful. Conclusion. Urinoma formed due to spontaneous rupture of collecting system based on ureteral obstruction caused by urinary bladder tumor is very rare clinical case scenario. In case of urinoma of unclear etiology invasive bladder cancer should be excluded.